A Prospective Study on the Influences of Workplace Stress on Mental Health - Babazono, Akira; Mino, Yoshio; Nagano, Jun; Tsuda, Toshihide; Araki, Tomoko (Journal of Occupational Health, 2005)
The purpose of this study was to clarify the influences of subjective stress in the workplace on mental health according to work contents in subjects without mental health problems. In a survey in fiscal 1997, 1,246 (84.6%) of all 1,363 workers of a manufacturing company in Japan, responded to a questionnaire including questions on subjective stress and GHQ60, and 1,135 workers answered all questions (effective response rate, 83.3%). In fiscal 1997, there were 705 "mentally healthy" workers with a GHQ score of :-16. of the 705 workers, 603 (85.5%) could be followed up by another survey 2 yr later (fiscal 1999). According to the contents of the work, multiple logistic regression analysis was performed using the status of mental health in fiscal 1999 as a dependent variable and subjective workplace stress, sex, age, smoking, and alcohol usage in fiscal 1997 as explanatory variables. The statistically significant items relating to problematic mental health for "factory work" were "too much competition", "feel pressed for time", and "cannot keep up with new technology" (Table 4). For "too much competition", the odds ratios (95% CI) of "always" and "sometimes" to "do not feel" were 4.04 (1.39-11.76) and 1.85 (0.92-3.70), respectively. For "feel pressed for time", the odds ratios (95% CI) of "always" and "sometimes" to "do not feel" were 2.40 (1.08-5.35) and 0.98 (0.46-2.06), respectively. For "cannot keep up with new technology", the odds ratio (95% CI) of "always" and "sometimes" to "do not feel" were 6. 54 (0.37-116.36) and 2.52 (1.34-4.77), respectively. The statistically significant items relating to problematic mental health for "research and development or office work" were "too much trouble at work" and "feel pressed for time". For "too much trouble at work", the odds ratios (95% CI) of "always" and "sometimes" to "do not feel" were 3.92 (1.41-10.93) and 1. 44 (0. 67-3.09), respectively. For "feel pressed for time", the odds ratios (95% CI) of "always" and "sometimes" to "do not feel" were 2.69 (1.04-6.93) and 2.09 (0.94-4.67), respectively. Our study suggests that subjective stress items aggravating mental health are different among work contents. If we could identify items of workplace stress influencing mental health by work contents, we could utilize the results for a mental health promotion program.